2001
DOI: 10.1080/096382801750058134
|View full text |Cite
|
Sign up to set email alerts
|

Students with disabilities: a national survey of participation in school activities

Abstract: Multivariate analysis revealed that school life in elementary, middle and high school could be defined by six distinct factors describing individual and group roles. Structural equation modelling yielded a second order latent variable that captured the complex and multi-dimensional aspect of participation, accounting for availability, eligibility, student characteristics/status, and student choice within a larger framework of participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(48 citation statements)
references
References 30 publications
3
44
0
1
Order By: Relevance
“…These results show some similarity with other research reported in the literature (Shields et al, 2006). These data are consistent with most research in the area, where the positive effect of participation in free time activities and recreation is mentioned as improving personal and social skills, health and wellbeing (Caldwell & Gilbert, 1990;King et al, 2003;Simeonsson et al, 2001). …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…These results show some similarity with other research reported in the literature (Shields et al, 2006). These data are consistent with most research in the area, where the positive effect of participation in free time activities and recreation is mentioned as improving personal and social skills, health and wellbeing (Caldwell & Gilbert, 1990;King et al, 2003;Simeonsson et al, 2001). …”
Section: Resultssupporting
confidence: 80%
“…Its positive influence on the development of personal, social and relational skills (Werner 1993;Simeonsson, Carlson, Huntington, McMillen & Brent, 2001), as well as health (King et al, 2003) has been highlighted and was considered an important predictor of personal well-being (Caldwell & Gilbert, 1990). …”
Section: Self-concept In Situations Of Risk and Socio-educational Actmentioning
confidence: 99%
“…Furthermore, the remaining environmental barrier identified (money to support child participation at home and in the community) is related to the affordability dimension of Maxwell and Granlund (2011) and Simeonsson and colleagues (Simeonsson et al, 2001) model. Affordability is conceptualized as a condition to participate and includes a subjective evaluation of financial constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Families need to make an overall positive assessment of conditions to participate (environmental factors) to provide children the opportunity to engage in diverse life situations. This model has been used to assess inclusive education (Simeonsson et al, 2001;Maxwell and Granlund, 2011), but assessments of home and community settings are also warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation